Chemical-imaging-guided optical manipulation of biomolecules - Clark, Matthew G.; Ma, Seohee; Mahapatra, Shivam; Mohn, Karsten J.; Zhang, Chi (Frontiers in Chemistry, 2023)
Chemical imaging via advanced optical microscopy technologies has revealed remarkable details of biomolecules in living specimens. However, the ways to control chemical processes in biological samples remain preliminary. The lack of appropriate methods to spatially regulate chemical reactions in live cells in real-time prevents investigation of site-specific molecular behaviors and biological functions. Chemical- and site-specific control of biomolecules requires the detection of chemicals with high specificity and spatially precise modulation of chemical reactions. Laser-scanning optical microscopes offer great platforms for high-speed chemical detection. A closed-loop feedback control system, when paired with a laser scanning microscope, allows real-time precision opto-control (RPOC) of chemical processes for dynamic molecular targets in live cells. In this perspective, we briefly review recent advancements in chemical imaging based on laser scanning microscopy, summarize methods developed for precise optical manipulation, and highlight a recently developed RPOC technology. Furthermore, we discuss future directions of precision opto-control of biomolecules.